The mediating role of employee engagement on factors affecting employee performance - Jacelyn Jacelyn; Alden Nelson (Universitas Ahmad Dahlan, 2023)
Employee performance is an essential aspect in determining the success of a company. Therefore, it is crucial to understand the factors influencing employee performance in the retail industry. This study aims to analyze the effect of talent management, knowledge management, and job satisfaction on employee performance, which is mediated by employee engagement. This research targets the population of employees working in the Kota Batam retail industry, which involves 270 respondents. Data for this study were collected using distributing questionnaires and processed using Partial Least Squares. This study found that employee engagement positively affects talent management, knowledge management, and job satisfaction. The other direct effect is that talent management and job satisfaction positively affect employee performance, but knowledge management has no effect. Talent management and job satisfaction mediated by employee engagement positively affect employee performance.